SISTEM PAKAR DIAGNOSA PENYAKIT JANTUNG DENGAN METODE CASE BASED REASONING (CBR) - Dona Dona; Hendri Maradona; Masdewi Masdewi (ZONAsi: Jurnal Sistem Informasi, 2021)
Heart disease is a disease that is very dangerous for human survival, therefore it must be addressed early on from the appearance of symptoms. Advances in expert systems can overcome this problem by designing a web-based computer system that uses databases and programming languages ​​such as PHP-MySQL so that it can help heart patients to diagnose the disease. The purpose of this research is to build a web-based expert system for diagnosing heart disease. Expert system application in this decision making uses the Case Based Reasoning (CBR) method, namely the method of making decisions by comparing new cases with old cases through four processes of retrieve, reuse, revise, and retain. Analysis and system design used are Context Diagram, Data FlowDiagram, Entity Relationship Diagram and Flowchart. In this expert system, the system will giving orders in the form of selecting the symptoms experienced, namely what symptoms are experienced. Then the patient selects the symptoms experienced by checking the symptoms experienced. The system will provide diagnostic results based on the symptoms experienced by the patient. Result diagnosis in the form of the type of heart disease experienced and the treatment solution and how much the percent chance the patient has the disease.